Common Creativity International: CC-licensing and Other Options for TEI-based Digital Editions in an International Context - Vanessa Hannesschläger (Journal of the Text Encoding Initiative)
In the digital age, the legal situation of the data produced in research projects that are relevant to an international research community such as the TEI is becoming more and more important. Because of differences in national laws, data produced and legally reusable in one country can be unprocessable in another. Therefore, ready-made licenses have become a powerful tool to facilitate digital research on an international scale. This paper discusses the concept of copyright in the context of global laws that make open licenses vital for ensuring the sustainability of (digital) research data. Three types of ready-made licenses (Creative Commons, Open Data Commons, and Digital Peer Publishing Licenses) and their specific strengths are examined. Finally, the history of the transformation of the abstracts of the 2016 TEI Conference and Members’ Meeting will serve as an example to show what proper licensing can do to push the research process.